Social and scientific knowledge in early childhood: an account of teaching practice in the context of the classroom (Research, Society and Development, 2020)
This article presents an experience report of a project carried out with students of kindergarten of a school in Niterói (RJ), from the continuous training course for teachers, promoted by the Brazilian Chemistry Association (ABQ) and the Niterói City Hall. This project sought to promote science education for children by correlating scientific literacy based on environmental issues. For such, the development of the activities occurred in three moments, in which diverse playful resources were used seeking to contribute in the construction of knowledge and critical sense of these children. The results point to the possibility of uniting science education and citizen education in early childhood education promoted by playful resources, favoring their interaction in activities, as well as a perception of their responsibilities and care for the environment in their childhood.